THE DEFINITION OF INDUSTRY PARK ELECTRICAL PRODUCTS - Kosenko, Oleksandra Petrivna; Kobielieva, Tetіana Oleksandrіvna; Tkachova, NadIya Petrivna (Науковий вісник Полісся, 2018)
The relevance of the research topic. Assessment and analysis of the Park of technological equipment is the basis for the development of the programme of action of each enterprise in the market for its products; it identifies the place and role of the enterprise in the economic system of society. Statement of the problem. The method of calculation of certain types of needs (e.g. the needs of the repair and maintenance of equipment) requires, as a mandatory stage of the calculation, the definition of a Park installed at the consumers. Analysis of recent researches and publications. Problems of definition of old machinery was considered by such scientists as Voronovsky G. K. [8], Gladenko I. V. [9], Kozicki D. [10], Pererva P. G. [11-12], Pogorelov N. I.[13], Savenkova O. N. [14], Tkachov M. M. [15], Tovazhnyanskiy V. L. [16]. Unsolved problems. Businesses and industries quantitation Park electrical products is not conducted as to determine it by direct counting almost impossible. Statement of the problem. The aim of the article is development of methodical provisions of the definition of industry Park electrical products that do not have independent technological purposes. The main results of the study. To determine industry Park electrical automation is proposed by studying their applicability (actual presence) in any one kind of the main process equipment industry Park which is known in advance or can be set in a scientific and proven methods. In particular, while defining industry Park low-voltage equipment as a basis we can take the main types of the main technological equipment, asynchronous motors with power up to 100 kW, the amount of generated or consumed in the sector of electricity, etc. the analysis of the coefficients of applicability of electrical equipment on different groups of cutting equipment is allowed to draw a conclusion about the different level of automation. Conclusions. Suggested in the article the technique of definition of industry Park electrical products is universal. After some modifications it can be used to determine the Park of any products that are components element of more complex technological equipment.